Toys go out : being the adventures of a knowledgeable Stingray, a toughy little Buffalo, and someone called Plastic - Jenkins, Emily, 1967- (Schwartz & Wade Books, 2006)
Six stories relate the adventures of three best friends, who happen to be toys.